Retrospective review of gunshot injuries at Salt River mortuary, Cape Town, Western Cape - Ramonyai, Jonathan (Department of Clinical Laboratory Sciences, 2024)
The use of firearms to inflict fatal trauma is a social, economic, and public health concern globally. In South Africa, firearm-related injuries (FRIs) have become the leading cause of unnatural death. Despite this, few studies have investigated the demographic, geographic and temporal distribution of firearm-related fatalities in South Africa. The aim of this study was to investigate fatal firearm-related injuries in forensic cases admitted to Salt River Mortuary in Cape Town, South Africa. A retrospective crosssectional study of fatal FRIs from Salt River Mortuary was conducted for the period 1 January 2017 to 31 December 2017. Autopsy case files were screened for fatalities associated with firearms. The following data were obtained from the database: demographics of the deceased, geographic and temporal distributions of firearmrelated deaths, the type of firearm used, projectile calibre, size of the entrance and exit wound, location of the injury, and blood alcohol concentration (BAC) of the deceased. In 2017, 3 658 autopsies were conducted at Salt River Mortuary in Cape Town, South Africa. More men (75%, n= 2 743) were admitted than women (23%, n= 843). The rate of firearm-related deaths during the period of investigation was 39.8/100 000 population of Salt River. Men (95%, n= 732) were mostly affected by firearm-related injuries compared to women (5%, n= 40). The relative risk of firearm-related deaths among men was 5.62 (p<0.001. Firearm-related homicide (97%, n= 751) was common and suicide cases were rare (2%, n= 19). All age groups were affected however, the highest proportion of deaths was identified in those between 21-30 years of age (42%, n= 325). Most deaths occurred in the Cape Flats with Mitchells Plain (18%, n= 108) as the most affected region. The highest proportion of injuries occurred in the upper limbs of the body (23%, n= 1056) followed by the head (22%, n= 1013). This study adds to the growing body of literature on the prevalence and characteristics of firearm-related deaths in South Africa. Firearm violence still appears to be a major public health and safety concern in Cape Town and further interventions should be developed to curb gun violence.